Recurrence, controllability, and stabilization of juggling. - Lynch, K.M (IEEE Transactions on robotics and automation)
This paper applies the idea of forced recurrence to demonstrate controllability and stabilizability of a single-input juggling system. Nonlinear optimization is used to find controls in a neighborhood of the recurrent controls that drive the system toward the goal trajectory. The approach is demonstrated on an experimental juggling system